2001
DOI: 10.1186/cc1044
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for delirium in the surgical intensive care unit

Abstract: CI = confidence interval; DG = delirious group; HBP = hepatobiliopancreatic diseases; ICU = intensive care unit; LSH = length of stay in hospital; LSICU = length of stay in the ICU; NDG = non-delirious group; OR = odds ratio. AbstractBackground Delirium is a sign of deterioration in the homeostasis and physical status of the patient. The objective of our study was to investigate the predisposing factors for delirium in a surgical intensive care unit (ICU) setting. Method Between January 1996 and 1997, we scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
56
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(66 citation statements)
references
References 31 publications
7
56
2
1
Order By: Relevance
“…It is recommended to screen patients' and careers' perspectives, and to reduce hospital costs, which can change the levels of prevention of delirium. Since the special nurses are frequently in a relationship with the patients, they play a key role in prevention, early detection, and treatment of patients with delirium (6)(7)(8)(9)(10). Although, the use of standard screening delirium patients in intensive care unit is not still common by physicians and nurses, it is necessary to screen delirium (3,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended to screen patients' and careers' perspectives, and to reduce hospital costs, which can change the levels of prevention of delirium. Since the special nurses are frequently in a relationship with the patients, they play a key role in prevention, early detection, and treatment of patients with delirium (6)(7)(8)(9)(10). Although, the use of standard screening delirium patients in intensive care unit is not still common by physicians and nurses, it is necessary to screen delirium (3,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…These factors include, but are not limited to: age, admission type, primary surgical procedure. These factors are recorded in electronic health records and have been used in the literature for delirium prediction (6, 12, 13). …”
Section: Introductionmentioning
confidence: 99%
“…EHR data are routinely collected for all patients at admission, and many studies have used them for prediction of health outcomes during and after the hospital stay (14). Previous works that have used EHR data for delirium prediction, have mainly used multivariate regression models due to their ease of interpretation and analysis (12, 13). Using logistic regression analysis, several other studies have identified important features in the preoperative dataset contributing to development of delirium, with up to 87% area under the receiver operating characteristics (ROC) curve (AUC) (12, 13, 15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations